2021
DOI: 10.3390/cancers13174344
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Multigene Germline and Parallel Somatic Genetic Testing in Epithelial Ovarian Cancer: SIGNPOST Study

Abstract: We present findings of a cancer multidisciplinary-team (MDT) coordinated mainstreaming pathway of unselected 5-panel germline BRCA1/BRCA2/RAD51C/RAD51D/BRIP1 and parallel somatic BRCA1/BRCA2 testing in all women with epithelial-OC and highlight the discordance between germline and somatic testing strategies across two cancer centres. Patients were counselled and consented by a cancer MDT member. The uptake of parallel multi-gene germline and somatic testing was 97.7%. Counselling by clinical-nurse-specialist m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 55 publications
(76 reference statements)
3
56
0
Order By: Relevance
“…Expansion in local laboratory infrastructure is needed to improve access and manage throughput, as genetic testing is currently mainly performed through laboratories at major hospitals affiliated with top-ranked universities [ 55 ]. Given the volume of BC cases diagnosed annually, newer implementation approaches such as ‘mainstreaming’ genetic counseling and testing, which have been successfully implemented across OC treatment pathways [ 56 ], will be needed for the successful large-scale implementation of testing at BC diagnosis too. Given the increasing applicability of genetics to cancer care and prevention, most cancer clinicians will need to be trained to improve their understanding of genetics and counsel patients.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion in local laboratory infrastructure is needed to improve access and manage throughput, as genetic testing is currently mainly performed through laboratories at major hospitals affiliated with top-ranked universities [ 55 ]. Given the volume of BC cases diagnosed annually, newer implementation approaches such as ‘mainstreaming’ genetic counseling and testing, which have been successfully implemented across OC treatment pathways [ 56 ], will be needed for the successful large-scale implementation of testing at BC diagnosis too. Given the increasing applicability of genetics to cancer care and prevention, most cancer clinicians will need to be trained to improve their understanding of genetics and counsel patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, beyond the LODs related to tumor cellularity, HRD assays evaluating tBRCA* barely detect LRs, although LRs are present in up to 16% of HGSOC patients, thus leading to false tBRCA wt statuses [ 33 ]. Recently, SIGNPOST showed that approximately 20% of gBRCA* was missed by the initial tBRCA* assessment, with the stunning revelation that none of the LRs of the cohort (representing 11% of gBRCA* ) were detected by the tBRCA* evaluation [ 138 ].…”
Section: Hrd Definitions: Current Technical Concerns and Perspectivesmentioning
confidence: 99%
“…BRIP1, RAD51C, and RAD51D have been suggested as the most important OCpredisposing genes, with 1.3%-4.3% of patients with OC having GPVs of BRIP1/RAD51C/RAD51D. 17,42,96,97 The estimated cumulative OC risks are 5.8%, 5.2%-11%, and 12% for mutant carriers of BRIP1 (to 80 years), 98 RAD51C, and RAD51D, 99,100 respectively. RRSO is currently recommended for carriers of BRIP1, RAD51C, and RAD51D mutations from the age of 45-50 years.…”
Section: Other Genes and Syndromes Associated With Gynecologic Cancermentioning
confidence: 99%
“…As each gene plays a different role in the HR pathway, phenotypes also differ. BRIP1 , RAD51C , and RAD51D have been suggested as the most important OC‐predisposing genes, with 1.3%–4.3% of patients with OC having GPVs of BRIP1/RAD51C/RAD51D 17,42,96,97 . The estimated cumulative OC risks are 5.8%, 5.2%–11%, and 12% for mutant carriers of BRIP1 (to 80 years), 98 RAD51C , and RAD51D , 99,100 respectively.…”
Section: Introductionmentioning
confidence: 99%